FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PROPERTI DAN REAL ESTATE DI INDONESIA - Teddy Chandra (EKUITAS (Jurnal Ekonomi dan Keuangan), 2014)
This research aims to analyze the factors affecting capital structure of property and real estate companies in Indonesia. The dependent variable used was DER, while the independent variable included profitability, growth opportunity, tangibility, size, dividend, liquidity, and business risk. The samples taken were the companies listed on the property and real estate sector of Indonesia Stock Exchange which were selected using purposive sampling. Among 47 companies listed on the property and real estate sector in the population, 8 companies were listed after January 2010, 1 company was delisting, and 1 company shifted to other sector. Hence, the samples used in this research were only 37 companies. The method used was linear regression. The result showed that profitability negatively influences capital structure; size and business risk have significant positive influence to the capital structure. On the other hand, growth opportunity, dividend, and liquidity do not have any significant influence on capital structure.